Pengaruh Pengungkapan ESG dan Karakteristik CEO Terhadap Kinerja Keuangan dan Kinerja Non Keuangan - Anida Nurul Hidayah; Asri Pangestika Lutfiani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This research aims to examine the influence of Environmental, Social, Governance (ESG) disclosure and Chief Excecutive Officer (CEO) characteristic to financial performance and non-finansial performance of companies listed on Indonesia Stock Exchange during the period 2023-2024. The methodology used is quantitative approach involving data collection from entire population of companies listed on Indonesia Stock Exchange using a sampling method based on purposive sampling techniques. The data used in this research is derived from secondary data. Analysis data method used in this research is multiple linear regression. The result of this research show that ESG disclosure has an effect of financial performance, CEO characteristic has no effect of financial performance and non-financial performance. This research has important implication for board practices in improving corporate performance through sustainability strategies.